\(\sqrt{5}+\sqrt{7}\)và \(\sqrt{12}\)
so sánh
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, \(\frac{3\sqrt{7}+5\sqrt{2}}{\sqrt{5}}=\frac{3\sqrt{35}+5\sqrt{10}}{5}=\frac{3\sqrt{35}+\sqrt{250}}{5}\)
Ta có: \(3\sqrt{35}< 3\sqrt{36}=3\cdot6=18< 18,5\)
\(\sqrt{250}< \sqrt{256}=16\)
\(\Rightarrow3\sqrt{35}+\sqrt{250}< 18,5+16=34,5\Rightarrow\frac{3\sqrt{35}+5\sqrt{10}}{5}< \frac{34,5}{5}=6,9\)
b,\(\sqrt{13}-\sqrt{12}=\frac{1}{\sqrt{13}+\sqrt{12}};\sqrt{7}-\sqrt{6}=\frac{1}{\sqrt{7}+\sqrt{6}}\)
Vì \(\sqrt{13}+\sqrt{12}>\sqrt{7}+\sqrt{6}\)nên \(\frac{1}{\sqrt{13}+\sqrt{12}}< \frac{1}{\sqrt{7}+\sqrt{6}}\)
\(\Rightarrow\sqrt{13}-\sqrt{12}< \sqrt{7}-\sqrt{6}\)
Lời giải:
\(2\sqrt{12}>2\sqrt{9}=2.3=6>3\)
\(\sqrt{6}> \sqrt{5}\)
\(\Rightarrow 2\sqrt{12}+\sqrt{6}> 3+\sqrt{5}\)
\(\left(\sqrt{2}+\sqrt{3}\right)^2=5+2\sqrt{6}>2^2=4\left(5>4\right)\\ \Leftrightarrow\sqrt{2}+\sqrt{3}>2\)
\(\left(\sqrt{8}+\sqrt{5}\right)^2=13+2\sqrt{40};\left(\sqrt{7}-\sqrt{6}\right)^2=13-2\sqrt{42}\\ 2\sqrt{40}>0>-2\sqrt{42}\\ \Leftrightarrow13+2\sqrt{40}>13-2\sqrt{42}\\ \Leftrightarrow\left(\sqrt{8}+\sqrt{5}\right)^2>\left(\sqrt{7}-\sqrt{6}\right)^2\\ \Leftrightarrow\sqrt{8}+\sqrt{5}>\sqrt{7}-\sqrt{6}\)
\(A=\sqrt{6+2\sqrt{5}}-\sqrt{5}=\sqrt{5}+1-\sqrt{5}=1\)
\(B=\sqrt[3]{7+5\sqrt{2}}-\sqrt{2}=\sqrt{2}+1-\sqrt{2}=1\)
Do đó: A=B
\(\sqrt{6+2\sqrt{5}}-\sqrt{5}=\sqrt{\left(\sqrt{5}+1\right)^2}-\sqrt{5}=\left|\sqrt{5}+1\right|-\sqrt{5}=1\)
\(\sqrt[3]{7+5\sqrt{2}}-\sqrt{2}=\sqrt[3]{\left(\sqrt{2}\right)^3+1^3+3.2+3\sqrt{2}}-\sqrt{2}=\sqrt[3]{\left(\sqrt{2}+1\right)^3}-\sqrt{2}=\sqrt{2}+1-\sqrt{2}=1\)
--> Bằng nhau
Ta có: \(12>9\)
\(6\sqrt{3}>4\sqrt{5}\)
Do đó: \(12+6\sqrt{3}>9+4\sqrt{5}\)
\(\Leftrightarrow\sqrt{12+6\sqrt{3}}>\sqrt{9+4\sqrt{5}}\)
\(A=\left(\sqrt{1}+\sqrt{2}+\sqrt{3}+\sqrt{4}\right)+\left(\sqrt{5}+\sqrt{6}+\sqrt{7}+\sqrt{8}+\sqrt{9}\right)+\left(\sqrt{10}+\sqrt{11}+\sqrt{12}\right)\)
Ta có:
\(\sqrt{1}+\sqrt{2}+\sqrt{3}+\sqrt{4}>1+\sqrt{1}+\sqrt{1}+\sqrt{1}+2=5\)
\(\sqrt{5}+\sqrt{6}+\sqrt{7}+\sqrt{8}+\sqrt{9}>\sqrt{5}+\sqrt{5}+\sqrt{5}+\sqrt{5}+\sqrt{5}=5\sqrt{5}\)
\(\sqrt{10}+\sqrt{11}+\sqrt{12}>\sqrt{9}+\sqrt{9}+\sqrt{9}=9\)
=> \(A>5+5\sqrt{5}+9=14+5\sqrt{5}>12+5\sqrt{5}\)
Vậy...
a) Ta có \(5=\sqrt{25}\)
Vì \(\sqrt{25}>\sqrt{11}\) nên \(5>\sqrt{11}\)
b) Ta có \(4=\sqrt{16}\)
Vì \(\sqrt{13}< \sqrt{16}\) nên \(\sqrt{13}< 4\)
c) Ta có \(-7=-\sqrt{49}\)
Vì \(-\sqrt{49}< -\sqrt{43}\) nên \(-7< -\sqrt{43}\)
d) Ta có \(-5=-\sqrt{25}\)
Vì \(-\sqrt{21}>-\sqrt{25}\) nên \(-\sqrt{21}>-5\)
\(\sqrt{5}>\sqrt{4}\)
\(\sqrt{7}>\sqrt{4}\)
\(=>\sqrt{5}+\sqrt{7}>\sqrt{4}+\sqrt{4}=4\)(1)
\(\sqrt{12}< \sqrt{16}=4\)(2)
từ (1(,(2)=> .....